Radiation-Induced Pulmonary Epithelial-Mesenchymal Transition: A Review on Targeting Molecular Pathways and Mediators - Nagaraja, Sunilgowda S.; Nagarajan, Devipriya (Current Drug Targets, 2018)
Background: Radiotherapy is the most widely used treatment method for average and advanced lung cancer patients. Moreover, the clinical toxicities caused by radiotherapy are categorized into acute radiation pneumonitis and late pulmonary fibrosis. Epithelial-mesenchymal transition (EMT) is a complex physiological process involves many signaling molecules and proteins like adaptor proteins, and transcriptional factors. It was identified as a significant mechanism for fibrosis, wound healing and also cancer. A variety of biomarkers have appeared in radiation-induced lung EMT, some of which are acquired (N-cadherin, vimentin and fibronectin, etc.) and some of which are repressed during the transition of epithelial cells (E-cadherin, zona occludens-1). Objective: In the current review, we highlighted the radiation-induced lung EMT signaling pathway and their mediators. We also discuss the EMT in cancer, fibrosis and its epigentics. Results: Radiation-induced lung EMT is controlled by numerous signaling pathways like MAPK, NF- ΚB, Wnt, microRNAs and histone modifications. Transcriptional factors such as Snail, slug, twist, ZEB1 (Zinc finger E-box binding-1) and ZEB2 (Zinc finger E-box binding-2) proteins are inducers linking radiation-induced EMT and fibrosis. Epigenetic modulations are heritable changes in the structure and function of the genome that occurs without any change in the sequence. Several approaches showed the role of epigenetic modifications and its inhibitors in controlling fibrosis and cancer. Only limited reports are focused on understanding the epigenetic regulations of radiation-induced lung EMT. Conclusion: The current review focused on recent findings regarding radiation-induced lung fibrosis and EMT, thus provides some information on important signaling pathways, its subsequent expression of genes and proteins involved in EMT. This review also discussed various inhibitors that could be used to treat EMT related diseases, i.e., fibrosis, cancer.
Keywords: EMT